ANALISIS KEMAMPUAN INTERPRETASI PESERTA DIDIK SMP PADA MATERI PERBANDINGAN - Desy Iryani; Ahmad Yani T (STKIP Singkawang, 2022)
This study aims to describe the interpretation ability of seventh grade students of SMP Negeri 3 Satu Atap Embaloh Hilir in comparative material. This type of research is a qualitative research designed to determine the students' interpretation ability in comparative material. Data collection techniques in the form of tests and interviews. The instrument used is in the form of an interpretation ability test, which amounts to 1 question. Interviews were conducted to further explore students' interpretation abilities. The research sample consisted of 1 student in the high category (YL), 1 student in the medium category (NR) and 1 student in the low category (NP). The results showed that (1) students in the high category (YL) in solving comparative material problems were able to understand the problem well, were able to interpret the data from the problem, were able to develop a plan of completion and carry out the appropriate settlement steps. (2) Students in the medium category (NR) are able to understand the problem quite well, but do not write down the information that is known and what questions are asked when solving comparative material problems, able to plan and implement a settlement plan in accordance with the completion steps and arithmetic operation rules. mix even though it's not quite right. (3) Students in the low category are unable to understand comparative material problems, are unable to plan and implement solutions, and are unable to evaluate and interpret the answers obtained.